2015
DOI: 10.1002/aur.1489
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Moderators of a Short Theory of Mind Intervention for Children with Autism Spectrum Disorder: A Randomized Controlled Trial

Abstract: Limited perspective taking or "Theory of Mind" (ToM) abilities are a core deficit of autism, and many interventions are aimed to improve ToM abilities. In this study, we investigated the effectiveness of a ToM treatment for children with autism spectrum disorders (ASD) and, for the first time, the moderating roles of social interaction style (SIS) and disruptive behavior (DB), to determine which children are most likely to respond to this intervention. The trial protocol is registered at www.trialregister.nl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 41 publications
1
57
0
1
Order By: Relevance
“…Previous data from this randomized control trial (RCT) showed that training improved children’s knowledge of ToM; ToM-related behavior also increased and autistic features decreased (Begeer et al 2015). A larger sample of participants from the same RCT has since become available, allowing us to test the potential moderating effects of these parental characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data from this randomized control trial (RCT) showed that training improved children’s knowledge of ToM; ToM-related behavior also increased and autistic features decreased (Begeer et al 2015). A larger sample of participants from the same RCT has since become available, allowing us to test the potential moderating effects of these parental characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Communication-focused interventions was used in twenty one studies [15,21,26,31,46,50,51,54,55,66,67,75,76,82,91,[93][94][95]104]. Thirty-two studies used integrative programs [18,20,24,25,28,30,33,[35][36][37]40,52,58,60,62,63,71,74,[77][78][79]81,86,89,92,96,98,[100][101][102][103]107]. Also, thirty studies used social skills development interventions [16,17,…”
Section: Resultsmentioning
confidence: 99%
“…The results of the included studies were mainly based on observed data and only in fourteen studies, selfreported of participants' practices were used to evaluate the effects of interventions [23,34,40,45,58,61,64,65,70,72,77,79,100,101]. Of the included studies, only twelve (12.9%) used theories and models.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (Table a–c) met inclusion criteria for targeting impaired social communication in ASD [12 psychosocial , two biomedical and one mixed biomedical/psychosocial intervention ]. Most recently published psychosocial interventions provided single study data evaluating unique intervention approaches with the exception of parent‐mediated (three trials) and computer‐based (three trials) approaches.…”
Section: Results and Clinical Practice Recommendationsmentioning
confidence: 99%
“…Two small computer‐based interventions focused on ToM training failed to bring about treatment effects on social communication outcomes , while a third small study found positive effects on social symptoms following a computer‐based social skills intervention; however, bias across studies was rated as unclear to high . Single study data also showed positive results following a number of other interventions on outcomes related to impaired social interaction, including: ToM intervention vs. waitlist , pivotal response therapy vs. parent education , CBT vs. facilitated play , behavioural therapy with speech‐generating support vs. behavioural therapy alone and a monthly play intervention vs. education .…”
Section: Results and Clinical Practice Recommendationsmentioning
confidence: 99%